Dose-Dependent Effects of Lipopolysaccharide on the Endothelium-Sepsis versus Metabolic Endotoxemia-Induced Cellular Senescence - Dennis Merk; Fiona Frederike Cox; Philipp Jakobs; Simone Prömel; Joachim Altschmied; Judith Haendeler (MDPI AG, 2024)
The endothelium, the innermost cell layer of blood vessels, is not only a physical barrier between the bloodstream and the surrounding tissues but has also essential functions in vascular homeostasis. Therefore, it is not surprising that endothelial dysfunction is associated with most cardiovascular diseases. The functionality of the endothelium is compromised by endotoxemia, the presence of bacterial endotoxins in the bloodstream with the main endotoxin lipopolysaccharide (LPS). Therefore, this review will focus on the effects of LPS on the endothelium. Depending on the LPS concentration, the outcomes are either sepsis or, at lower concentrations, so-called low-dose or metabolic endotoxemia. Sepsis, a life-threatening condition evoked by hyperactivation of the immune response, includes breakdown of the endothelial barrier resulting in failure of multiple organs. A deeper understanding of the underlying mechanisms in the endothelium might help pave the way to new therapeutic options in sepsis treatment to prevent endothelial leakage and fatal septic shock. Low-dose endotoxemia or metabolic endotoxemia results in chronic inflammation leading to endothelial cell senescence, which entails endothelial dysfunction and thus plays a critical role in cardiovascular diseases. The identification of compounds counteracting senescence induction in endothelial cells might therefore help in delaying the onset or progression of age-related pathologies. Interestingly, two natural plant-derived substances, caffeine and curcumin, have shown potential in preventing endothelial cell senescence.